Clean hydrogen production in a full biological microbial electrolysis cell - Jafary, T. (Elsevier Ltd, 2018)
The recent interest in microbial electrolysis cell (MEC) technology has led the research platform to develop full biological MECs (bioanode-biocathode, FB-MEC). This study focused on biohydrogen production from a biologically catalyzed MEC. A bioanode and a biocathode were initially enriched in a half biological MFC (bioanode-abiocathode, HB-MFC) and a half biological MEC (abioanode-biocathode, HB-MEC), respectively. The FB-MEC was established by transferring the biocathode of the HB-MEC and the bioanode of the HB-MFC to a two-chamber MEC. The FB-MEC was operated under batch (FB-MEC-B) and recirculation batch (FB-MEC-RB) modes of operation in the anodic chamber. The FB-MEC-B reached a maximum current density of 1.5 A/m2 and the FB-MEC-RB reached a maximum current density of 2.5 A/m2 at a similar applied voltage while the abiotic control system showed the maximum of 0.2 A/m2. Hydrogen production rate decreased in the FB-MEC compared to that of the HB-MEC. However, the cathodic hydrogen recovery increased from 42 obtained in the HB-MEC to 56 in the FB-MEC-B and 65 in the FB-MEC-RB, suggesting the efficient oxidation and reduction rates in the FB-MEC compared to the HB-MEC. The onset potential for hydrogen evolution reaction detected by linear sweep voltammetry analysis were -0.780 and -0.860 V vs Ag/AgCl for the FB-MEC-RB and the FB-MEC-B (-1.26 for the abiotic control MEC), respectively. Moreover, the results suggested that the FB-MEC worked more efficiently when the biocathode and the bioanode were enriched initially in half biological systems before transferring to the FB-MEC compared to that of the simultaneously enriched in one system. Â© 2018 Hydrogen Energy Publications LLC.